The Model Of Digital Marketing And Electronic Word Of Mouth Communication - Boyke Setiawan Soeratin; Nandan Limakrisna; Andyan Pradipta Utama; Nana Trisnawati; Muhammad Millah Irsyaddin (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this study is to test whether digital marketing and electronic word-of-mouth influence purchase decisions. The type of research used in this study is quantitative research. The subjects of this study were students of the Faculty of Economics and Business, Winaya Mukti University, Bandung. The data collection method used a questionnaire survey with a sample of 100 respondents using the Tokopedia marketplace for FEB UNWIM Bandung students. Data analysis used in this study was multiple linear regression analysis with the SPSS 26.0 program. The results of this study indicate that digital marketing and e-WOM variables have a positive and significant impact on the purchasing decisions of Tokopedia market users among FEB UNWIM Bandung students.